Concept Note: Development of Climate Risk Profiles for Agricultural Commercialization Clusters (ACC) - Alliance of Bioversity International and CIAT (2020)
To support the mainstreaming of climate into the Agricultural Commercialization Clusters (ACC) prioritized value chain compacts (wheat, maize, sesame, malt barley and horticulture crops – tomato, onion, banana, mango and avocado) the International Center for Tropical Agriculture (CIAT) proposes to develop climate risk and adaptation opportunity assessments for agricultural value chains. The analyses will be in the form of a Climate Risk Profile for ACC areas that will promote a tailored approach focusing on an assessment of exposure to climate risk, causes of vulnerabilities for value chains, and options for climate adaptation and resilience-building technologies and practices. These Climate Risk Profiles will systematically describe key climate vulnerabilities, entry points for CSA in the ACC value chains, policy/institutional enabling conditions, and co-finance opportunities along the value chain. These profiles will take a full value chain approach assessing these issues from variety selection and provision of inputs, to on-farm production, to harvest storage and marketing tailored to agro-ecological contexts across the clusters. The development of the Climate Risk Assessment Profiles will build on past work conducted by CIAT and the CGIAR Researcg Program on Climate Change, Agriculture and Food Security (CCAFS), to develop Climate Smart Agriculture Country Profiles in collaboration with the World Bank and other partners including FAO, USAID, DFID, among others.